Social Support and Affective Commitment: Mediation Mechanisms of Relational Attachment - Dewi Atmi Dilla; Haznil Zainal (SAINS ORGANISASI, 2022)
This study aims to determine whether social support has an effect on affective commitment and whether relational attachmen is able to mediate the relationship between social support and affective commitment to employees. Sources of data in this paper are primary data. With 99 employees as the writing sample. Analysis of the data used in this paper is PLS Structural Equation Modeling (SEM) which is operated through the WarpPLS program. The results showed that social support had a positive and significant effect on relational engagement, relational attachment had a positive and significant effect on affective commitment, and relational attachment was able to mediate social relationships support affective commitmen.